Fungal burden exposure assessment in podiatry clinics from Ireland. Issue 2 (4th March 2018) - Viegas, Carla; Coggins, Ann Marie; Faria, Tiago; Caetano, Liliana Aranha; Gomes, Anita Quintal; Sabino, Raquel; Verissimo, Cristina; Roberts, Nigel; Watterson, David; MacGilchrist, Claire; Fleming, Gerard T.A.
ABSTRACT: Fungi are amongst the bioaerosols of most importance, as indicated by the growing interest in this field of research. The aim was to characterize the exposure to fungal burden in podiatry clinics using culture-based and molecular methods. Methods: Airborne fungi were collected using an impaction air sampler and surface samples were also performed. Fourteen air samples were collected for direct detection of fungal DNA from filamentous fungi and dermatophytes. Overall, 63.6 % of the evening samples and 46 % of the morning samples surpassed the threshold values (150 CFU/m 3 ). Molecular detection, by real time PCR, of the target fungal species/strains ( Aspergillus and Stachybotrys species) was negative for all samples collected. Trichophyton rubrum was detected by PCR analysis in one DNA sample collected on day six. Results suggest the use of both culture-based and molecular methodologies are desirable for a complete evaluation of fungal burden in this particular health care setting.